Pengalihan Hak Hadhanah Jatuh kepada Bapak terhadap Anak Belum Mumayyiz (Studi Kasus di Pengadilan Agama Palangka Raya) - Sanawiah Sanawiah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
As a result of divorce, other problems also arise as a result of being granted divorce claims, both the issue of joint assets to the problem of who is more entitled to do hadhanah (maintenance) of children. In Compilation of Islamic Law Article 105 letter (a) states that in the event of divorce, the maintenance of a child who has not been mumayyiz or has not been 12 (twelve) years old is the right of his mother, then, in Article 156 letter (a) due to the termination of marriage child who hasn't mumayyiz entitled to hadhanah from his mother. The method in this dissertation research uses the type of legal research empiric research that takes place in the field, with the approach of legislation (statute approach), conceptual approach (conceptual approach), and approach (prophetic) prophetic approach is an approach with basis instrument sourced texts from the revelations received by prophets and apostles and the Sunnah. The first research problem was why Hadhanah's rights fell to the father of children who were not yet mumayyiz and the second was how the Judge's policy in deciding on hadhanah cases in the Palangka Raya Religious Court Number 0067/Pdt.G/2018/PA Plk.